Food allergy spectrum in the tropic: clinical and epidemiological profiles in a colombian hospital. A cross-sectional study - Olaya-Hernandez, Manuela; Vasquez, Laura Del Mar; Silva, Diana Lucia; Martinez-Betancur, Sofia; Guerra, Maria; Arias, Oriana; Ramirez, Luis Fernando; Serrano, Carlos Daniel (Frontiers in Immunology, 2023)
Introduction Food allergy affects 2-10% of the general population; it is more frequent among children than among adults, and it is one of the leading causes of anaphylaxis. Diagnosis of food allergy requires a detailed medical history, skin tests, specific immunoglobulin E (IgE) tests for the food involved, and an oral challenge as final confirmation. Objectives This study aimed to describe the clinical and epidemiological characteristics of patients who underwent oral food challenges for suspected food allergies in a reference center in Colombia. Methodology An observational, descriptive, cross-sectional and retrospective study was conducted. Data were retrospectively collected from patients who were evaluated in the allergology service and suspected of food allergy from 2011 to 2018. Quantitative variables are presented as means or medians depending on the normality of the distribution (assessed by the Shapiro-Wilk test), and categorical variables are presented as frequencies and percentages. Results A total of 215 controlled open challenges were performed on 176 patients, most of whom were children (69%). Thirty-one patients (17%) required another oral challenge with a second food, and 11 (6.25%) required another oral challenge with three foods. Twelve oral challenges (5.58%) were positive. Of these, five challenges were positive for cow’s milk, 5 were positive for shrimp, and 2 were positive for legumes (peanuts and lentils). Conclusion The frequency of confirmed food allergies and the profile of food allergies in our population differs from that reported in other parts of the world.